2012
DOI: 10.1038/ejhg.2012.124
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype analysis of the 185delAG BRCA1 mutation in ethnically diverse populations

Abstract: The 185delAG* BRCA1 mutation is encountered primarily in Jewish Ashkenazi and Iraqi individuals, and sporadically in non-Jews. Previous studies estimated that this is a founder mutation in Jewish mutation carriers that arose before the dispersion of Jews in the Diaspora B2500 years ago. The aim of this study was to assess the haplotype in ethnically diverse 185delAG* BRCA1 mutation carriers, and to estimate the age at which the mutation arose. Ethnically diverse Jewish and non-Jewish 185delAG*BRCA1 mutation ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…Using haplotype analysis of individuals from diverse and unlikely related ethnicities may allow for distinguishing some of these possibilities. Indeed, haplotype analysis of the c.66_67del BRCA1 PSV has shown that among Ashkenazi Jews, non‐Ashkenazi Jews, and non‐Jewish Hispanics, the PSV has a common haplotype, whereas the haplotype in Malaysians and English non‐Jews is distinct (Laitman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Using haplotype analysis of individuals from diverse and unlikely related ethnicities may allow for distinguishing some of these possibilities. Indeed, haplotype analysis of the c.66_67del BRCA1 PSV has shown that among Ashkenazi Jews, non‐Ashkenazi Jews, and non‐Jewish Hispanics, the PSV has a common haplotype, whereas the haplotype in Malaysians and English non‐Jews is distinct (Laitman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of substantial information regarding cancer risks in BRCA1/2 PSV carriers, the amount of information available to suggest that this PSV arose no more than 1500 years ago, suggesting that it was transmitted from the middle east to Africa, and did not arise there before the original migration of individuals out of Africa (Laitman et al, 2013). However, this PSV has been reported in native Africans (Zoure et al, 2018) and has arisen in multiple populations independently, so it is not known whether this PSV is a new PSV at a locus that demonstrates high mutation rates, or if it is the common Jewish founder PSV, which has been observed in Middle Eastern or North African populations (Laitman et al, 2013;Slaoui et al, 2014;Zoure et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…43,4547,50,5658 One of the 3 Jewish founder mutations, BRCA1 185delAG is estimated to have arisen about 800 years ago or earlier and is believed to have been introduced into Latin America about 650 years ago. 59 When this mutation is identified in Latinos, haplotype analysis supports that this mutation is of the same origin as the Jewish founder mutation, rather than a separate genetic event. 60,61 Pooled mutation estimates performed by Porchia et al 55 found that BRCA1 185delAG is the second most prevalent BRCA1 mutation and its frequency is not significantly different between Mexico and other Latin American countries ( P = .70).…”
Section: High and Moderate Penetrance Genesmentioning
confidence: 95%